Developing Digital Empowerment Programs to Enhance the Marketing Performance of Private Islamic Higher Education Institutions - Riofita, Hendra (Muslim Business and Economics Review, 2022)
The sustainability of higher education should be supported by marketing strategies that enhance marketing performance and attract a higher number of prospective students. Considering the decision of prospective students to attend a particular institution is always motivated by the information they obtain on that institution’s achievements, this study aims to develop digital network empowerment and digital information sharing activities based on the resource-based view model. In addition, considering digital services have not yet had a conclusive effect on marketing performance, this study also aims to develop digital service recovery to enhance the effect of digital network empowerment and digital information sharing on marketing performance. Primary data were collected using a questionnaire sent to the management teams of Indonesian private Islamic higher education institutions via a Google form link. The data were processed using SPSS and Amos. The findings demonstrate that digital network empowerment and digital information sharing have a very significant effect on marketing performance, but digital service recovery does not. However, digital service recovery has a very significant effect on digital network empowerment and digital information sharing. The findings illustrate that digital network empowerment and digital information sharing can contribute to the resource-based view model to enhance marketing performance.